Design analysis of web-based furniture marketing information system - Ayshwarya B.; Nguyen P.T.; Alismi; Abadi S.; Shankar K.; Hashim W.; Korostelev A.A.; Maseleno A. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
In the industrial world and with the progress of the times, technology will greatly help a small industry in managing beneficial information for consumers. Not all wood furniture industries have stores. However, the majority of shop owners in Pringsewu do not produce their own furniture. The owners who do not produce their own furniture receive merchandise from entrepreneurs who do not have shops. The owners provide furniture model orders needed by customers and users. In this case study, the data had been computerized so that consumers can receive information only by accessing the desired information. Furniture stores that build Web-Based Furniture Marketing Information Systems id to participate in providing data and information to people and can be accessed quickly, anywhere, and anytime. BEIESP.